Metadiscursidade, argumentação e referenciação - Cavalcante, Mônica Magalhães (2009)
We discuss in this work the notion of metadiscursivity, which has been sustained in the work of Hyland. In this approach are involved aspects of textual structure that go beyond the content and show the communicative and social engagement of the enunciator in what he enunciates to the co-enunciator. The author sees as metadiscursive every strategy used by the enunciator to project his communicative intentions in the enunciate. However, when analyzing the data, Hyland restricts the scope of the phenomenon, conditioning it to the occurrence of expressions indicating the stance of the enunciator and the engagement of the co-enunciator. We will show from excerpt of texts of various genres that referential expressions can play the role of such metadiscursive expedients, which collaborate on the effectiveness of an argumentative text.